Immune-Related Dermatologic Reactions in Cancer Patients Undergoing Immunotherapy: A Case Series - Chhabra, Raja; Dodagoudar, Chandragouda; Rajpurohit, Sajjan; Vidushi, Aditya; Kumari, Versha; Osama, Md Ali (Indian Journal of Medical and Paediatric Oncology, 2025)
Immune checkpoint inhibitors (ICIs) have transformed the treatment paradigm across various malignancies by reactivating T cell responses against tumor cells. These agents function by blocking inhibitory checkpoint pathways, thereby preventing immune downregulation and enhancing antitumor immunity. Despite their clinical success and relatively favorable safety profile, ICIs are associated with immune-related adverse events (irAEs), which can impact multiple organ systems. Among these, cutaneous irAEs are some of the most common, owing to the skin's immunologic sensitivity. These manifestations range from mild conditions—such as pruritus, maculopapular rashes, and inflammatory dermatoses including eczema, psoriasis, and lichenoid reactions—to more severe immunobullous disorders (such as bullous pemphigoid, pemphigus vulgaris, and Stevens–Johnson syndrome). While most cutaneous irAEs can be effectively managed without interrupting immunotherapy, certain cases may require prompt, multidisciplinary intervention to prevent serious complications. This case series presents four diverse malignancies complicated by dermatologic irAEs, highlighting atypical presentations, critical warning signs, and evidence-based strategies for management. Through these cases, we aim to raise awareness about less common cutaneous toxicities and offer practical guidance to ensure safe continuation of cancer immunotherapy.
Keywords: dermatology; immune checkpoint inhibitors; immune-related adverse events